STEP-BY-STEP INTRODUCTION OF ISLAMIC BANKING PRODUCTS AND THE “ISLAMIC WINDOW” MODEL (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
this article examines the institutional, prudential, operational, and market prerequisites for the phased introduction of Islamic banking products and the Islamic window model within dual financial systems. The study systematizes contemporary international experience, evaluates the compatibility of Shariah-compliant instruments with existing banking infrastructures, and proposes a sequenced implementation framework that balances financial inclusion, regulatory proportionality, consumer protection, and systemic stability. The paper argues that a carefully staged Islamic window approach can serve as a lower-friction transition mechanism for emerging markets, particularly Uzbekistan, by enabling demand testing, governance standardization, and gradual ecosystem formation before full-fledged Islamic banking expansion.